Audit of preoperative localisation of tumor with tattoo for patients undergoing laparoscopic colorectal surgery. Issue 3 (August 2016) - Saleh, A; Ihedioha, U; Babu, B; Evans, J; Kang, P
Background: Preoperative localisation of tumour is an essential requirement in laparoscopic colorectal surgery. Since the introduction of laparoscopic colorectal resections in NGH in February 2010, the difficulties of tumour localisation at the time of surgery without tattoo have been highlighted. Furthermore, endoscopic documentation of site of tattoo with respect to the tumour can be inconsistent and at times misleading or difficult to interpret. Tattooing guidelines should be simple to follow and consistent for all lesions irrespective of the location of the tumour. The recommendations were to place at least three spots of tattoo one mucosal fold distal to the lesion and clearly document site of tattoo with respect to tumour in the endoscopy report. Method: We identified 100 patients undergoing elective laparoscopic colorectal cancer resections over a two-year period. Data were collected regarding presence of tattoo preoperatively as documented in the colonoscopy report and subsequently the visibility of the tattoo at time of laparoscopy and its accuracy in relation to the tumour. Abdominoperineal resections and emergency colorectal operations were excluded. Results: Only 59% of the patients had a visible and accurate tattoo. In 17% of the patients, the tattoo was not visible at all, although it was documented in the endoscopy report that it had been administered. In 4% of patients, it was visible but inaccurately placed. In 20% of the patients, there were no tattoos at all, necessitating on table endoscopy and intraoperative specimen analysis to confirm that the tumour/lesion was within the resection specimen. Discussion: Preoperative tumour localisation is extremely important to correctly identify the site of tumour or lesion at laparoscopy. A standardised departmental protocol should be implemented by all endoscopists to place three spots of tattoo one mucosal fold distal to any significant lesions found. Failure to tattoo lesions/cancers preoperatively can lead to intraoperative delays and potential harm to patients from on-table endoscopy.